The last little secret - Day, Zuri (Day, Zuri. Sin City secrets, 2021)
Thanks to a year-long hiatus, interior designer Samantha Price is desperate for a new project. But the only client she can land is Nick Breedlove, a former one-night stand who<U+2019>s dominated her fantasies ever since! The real estate billionaire agrees their partnership is strictly professional<U+2014>even as his flirting promises more. If Sam gives in to their passion<U+2026>will Nick learn the truth about their baby son?